TINJAUAN YURIDIS PENERAPAN PERATURAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2017 TENTANG PEDOMAN MENGADILI PERKARA PEREMPUAN BERHADAPAN DENGAN HUKUM DALAM KASUS BAIQ NURIL - Defi, Delvita Eri; R, Mukhlis; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research discusses the application of Supreme Court Regulation No.3 of 2017 concerning Guidelines for Adjudicating Women's Cases in Contrasts with the Law. This Supreme Court Regulation (PERMA) contains the basics in the concept of gender equality, how judges should behave and what judges should not do in court. One example of a case that does not apply the Supreme Court regulation (PERMA) Number 3 of 2017 concerning Guidelines for Adjudicating Women's Cases against the Law, namely, the case of Baiq Nuril Maknun in Cassation Decision 574.K / Pid.Sus / 2018. Where in this case, Baiq Nuril Maknun is a woman who is facing the law for a case of verbal sexual violence by her superior, Haji Muslim. However, the victim was instead made the perpetrator based on what he had done in order to defend his dignity. The purposes of writing this thesis are: First, to find out the application of Supreme Court Regulation Number 3 of 2017 concerning Guidelines for Adjudicating Women's Cases Against the Law in the Baiq Nuril Maknun case. Second, to find out the legal consequences for the victim's cassation decision in the Baiq Nuril Maknun case who did not pay attention to Supreme Court Regulation Number 3 of 2017 concerning Guidelines for Adjudicating Women's Cases Against the Law in terms of Victim Blaming.The type of research used in this legal research is the normative juridical method. The data analysis used is qualitative analysis. In drawing conclusions, the author uses the deductive thinking method, which is a way of thinking that draws conclusions from general statements or propositions into certain statements. From the research results, there are two main points that can be concluded. First, justice for the defendant Baiq Nuril Maknun in decision Number 574.K / Pid.Sus / 2018 has not been fulfilled, because the Supreme Court judge (MA) in deciding the Baiq Nuril Maknun case did not apply or was not guided by the Supreme Court Regulation Number 3 of 2017 concerning Guidelines for Adjudicating Women's Cases against the Law. so that the objectives of the law do not achieve a sense of justice, legal certainty and benefit. Second, the legal consequences for the victim, namely the convicted person Baiq Nuril Maknun, the judge did not side with the victim, blaming the victim (victim blaming), namely Baiq Nuri Maknun as the perpetrator. Resulting in Baiq Nuril Maknun as a victim of verbal sexual violence against the victim's physical, psychological and social conditions. Keywords: Victim- Sexual Violence- Victim Blaming